2022
DOI: 10.3758/s13428-022-01923-3
|View full text |Cite
|
Sign up to set email alerts
|

Polish norms for a set of colored drawings of 168 objects and 146 actions with predictors of naming performance

Abstract: In this study, we present the first database of pictures and their corresponding psycholinguistic norms for Polish: the CLT database. In this norming study, we used the pictures from Cross-Linguistic Lexical Tasks (CLT): a set of colored drawings of 168 object and 146 actions. The CLT pictures were carefully created to provide a valid tool for multicultural comparisons. The pictures are accompanied by norms for Naming latencies, Name agreement, Goodness of depiction, Image agreement, Concept familiarity, Age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 120 publications
1
4
1
Order By: Relevance
“…In line with previous reports (Alario & Ferrand, 1999;Pompéia et al, 2001;Pind et al, 2000;Sanfeliu & Fernandez, 1996;Snodgrass & Vanderwart, 1980;Wolna et al, 2022), and as expected, we found negative correlations between the H-statistic and the percentage name agreement in the noun corpus. The nouns showed significant correlations between the psycholinguistic variables, except for image agreement which did not show any significant correlation with the remaining variables.…”
Section: Correlations Between Variables (Nouns)supporting
confidence: 93%
“…In line with previous reports (Alario & Ferrand, 1999;Pompéia et al, 2001;Pind et al, 2000;Sanfeliu & Fernandez, 1996;Snodgrass & Vanderwart, 1980;Wolna et al, 2022), and as expected, we found negative correlations between the H-statistic and the percentage name agreement in the noun corpus. The nouns showed significant correlations between the psycholinguistic variables, except for image agreement which did not show any significant correlation with the remaining variables.…”
Section: Correlations Between Variables (Nouns)supporting
confidence: 93%
“…The lack of results may be explained by the generally noisy and challenging environment because data were collected during scanning. It is also important to note that even though participants were instructed to name pictures as quickly as possible, overall naming speed (1072ms for L1 after L1 and 1075ms for L1 after L2) was slower than what is usually observed for L1 naming for this particular dataset (897ms; Wolna et al, 2022). The general slow-down of naming in L1 may have obscured the behavioral effect, which usually is quite small (~50ms).…”
Section: Behavioral Resultsmentioning
confidence: 78%
“…In the second block of each session, participants were asked to name pictures in L1. Each block contained 55 colored pictures representing objects (from the CLT database: Haman et al, 2015; Wolna et al, 2022). Pictures were not repeated between blocks.…”
Section: Methodsmentioning
confidence: 99%
“…In each session, participants named one block of pictures corresponded to one functional run. Each block was composed of 55 coloured pictures representing objects (from the CLT database 81 ). Pictures were not repeated between blocks.…”
Section: Methodsmentioning
confidence: 99%